Comorbid Bipolar and Alcohol Use Disorder—A Therapeutic Challenge - Grunze, Heinz; Schaefer, Martin; Scherk, Harald; Born, Christoph; Preuss, Ulrich W. (Frontiers in Psychiatry, 2021)
Comorbidity rates in Bipolar disorder rank highest among major mental disorders, especially comorbid substance use. Besides cannabis, alcohol is the most frequent substance of abuse as it is societally accepted and can be purchased and consumed legally. Estimates for lifetime comorbidity of bipolar disorder and alcohol use disorder are substantial and in the range of 40-70%, both for Bipolar I and II disorder, and with male preponderance. Alcohol use disorder and bipolarity significantly influence each other’s severity and prognosis with a more complicated course of both disorders. Modern treatment concepts acknowledge the interplay between these disorders using an integrated therapy approach where both disorders are tackled in the same setting by a multi-professional team. Motivational interviewing, cognitive behavioural and socio- therapies incorporating the family and social environment are cornerstones in psychotherapy whereas the accompanying pharmacological treatment aims to reduce craving and to optimize mood stability. Adding valproate to lithium may reduce alcohol consumption whereas studies with antipsychotics or naltrexone and acamprosate did not affect mood fluctuations or drinking patterns. In summary, there is a continuous need for more research in order to develop evidence-based approaches for integrated treatment of this frequent comorbidity.